Genomic consequences of açaí extraction in the Amazon: insights into selective pressures, genomic diversity, and population structure - Francisconi, Ana Flávia; Scaketti, Matheus; Morales-Marroquín, Jonathan Andre; de Carvalho, Igor Araújo Santos; Fornazier, Gabriela de Oliveira; Malaquias Costa, Flaviane; Moro, Matheus Sartori; Ferreyra Ramos, Santiago Linorio; Lopes, Maria Teresa Gomes; Zucchi, Maria Imaculada (Frontiers in Plant Science, 2025)
Among the most important non-timber forest products is the açaí fruit (Euterpe oleracea). In recent years, açaí production in Brazil has increased by 80.3%. This intensification has been accompanied by changes in biodiversity and forest structure, particularly in areas where extractive practices are prevalent. However, it remains unclear whether and how this intensification has affected the population genomics of E. oleracea. To address this, we collected samples from natural populations in the western Amazon (Amazonas state), where extractivism is lower, and in the eastern Amazon (Pará and Maranhão states), where extractive production is more intense. Using single nucleotide polymorphism (SNP) markers, we analyzed selective pressures, genomic diversity, and population structure between and within these regions. We detected a higher number of unique selection signals in the eastern Amazon, whereas only a slight reduction in genomic diversity was observed. In the west, genetic similarity between distant sites and an absence of correlation between genetic and geographic distance were identified. In the east, two genomic clusters were detected, and the group with higher extractive production showed signs of isolation. These findings reveal that the intensification of açaí extraction in the eastern Amazon has likely begun generating distinct selection signatures. Despite these localized signals of selection, overall genetic diversity remains high, probably due to biological and ecological buffering. In contrast, genomic similarity between distant western populations suggests recent human-mediated dispersal associated with cultivation. In the eastern Amazon, the observed genomic isolation emphasizes the need to maintain gene flow and reduce localized extraction pressure to ensure the long-term sustainability of this keystone Amazonian species.